2010
DOI: 10.1016/j.bbadis.2009.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in amyotrophic lateral sclerosis

Abstract: The etiology of motor neuron degeneration in amyotrophic lateral sclerosis (ALS) remains to be better understood. Based on the studies from ALS patients and transgenic animal models, it is believed that ALS is likely to be a multifactorial and multisystem disease. Many mechanisms have been postulated to be involved in the pathology of ALS, such as oxidative stress, glutamate excitotoxicity, mitochondrial damage, defective axonal transport, glia cell pathology and aberrant RNA metabolism. Mitochondria, which pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 118 publications
(127 reference statements)
4
142
0
2
Order By: Relevance
“…Although there is no consensus about the exact role of mitochondrial abnormalities [61], it is accepted that mitochondrial dysfunction is an important hallmark of ALS pathogenesis [5,62,63]. Several authors have shown deficits in mitochondrial function in the spinal cord and muscles of both human patients [64] and animal models of ALS [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus about the exact role of mitochondrial abnormalities [61], it is accepted that mitochondrial dysfunction is an important hallmark of ALS pathogenesis [5,62,63]. Several authors have shown deficits in mitochondrial function in the spinal cord and muscles of both human patients [64] and animal models of ALS [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence of mitochondrial abnormalities, morphologic and bioenergetic, are observed in human familial and sporadic ALS, as well as in many of the cell-culture and rodent models of SOD1-linked ALS (25,55). Like the wild-type protein, familial ALS-linked mutant SOD1 also accumulates in mitochondria, where it is thought to contribute directly to disease pathogenesis.…”
Section: Mutant Sod1 and Mitochondrial Dysfunction In Familial Alsmentioning
confidence: 99%
“…In addition, functional abnormalities of the mitochondria were described in the CNS, liver and muscle of SALS patients 10,11,14 . These changes suggest that the neurochemical basis for the observed morphological changes are widespread among different tissues and may consist in impaired mitochondrial bioenergetics, loss of membrane potential, reduced calcium buffering capacity and disrupted calcium homeostasis 29 .…”
mentioning
confidence: 99%